Construct Validity and Test-Retest Reliability of the International Fitness Scale (Ifis) in Colombian Children and Adolescents Aged 9-17.9 Years: The Fuprecol Study - Garcia-Hermoso, A (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Sin Resumen Disponible